KEBUTUHAN AIR BERSIH MASYARAKAT DI KABUPATEN KEPULAUAN ANAMBAS - Hernaningsih, Taty; Yudo, Satmoko (Jurnal Air Indonesia, 2015)
Kabupaten of Anambas Island consists of small islands with a catchment area is minimal; therefore the availability of clean water for public water needs cannot be available at certain seasons. Water problems in Anambas especially in spring sources is a decrease in discharge of springs (water crisis) as well as damage to the Watershed (DAS). Only in District Tarempa who have a water treatment system, while the population of the other islands to get water from springs or surface water through pipes that are built individually and communally without any water treatment. The population and activities of community in Anambas increased very rapidly while the infrastructure provided by the local government has not been adequate. In anticipation of these developments required a good city planning, particularly in the provision of clean water for people in Anambas Island. To determine how much water needs of the community in Anambas, should be calculated based on the population and projected water demand per person in accordance with standards established by Directorate General of Human Settlements Ministry of Public Works. The method used in calculating the projected water demand is the statistical method (arithmetic, least squares, geometric, or by using the trend of population growth in the form of regression method). Projected water demand results from the year 2013 to the year 2032 which has been calculated is Kecamatan Siantan, Central Siantan, Siantan East, South Siantan, Palmatak, Jemaja, East Jemaja and small islands with limited water availability. Based on the calculation of the projected water needs of the population, it has made planning the installation of water treatment plants following its installed capacity is achieved in stages in order to provide water services to all residents in Anambas Island. Keywords : Water resources, statistic method, installed capacity.